Ethnic Variations in Radiographic Parameters and SRS-22 Scores in Adult Spinal Deformity: A Comparison Between North American and Japanese Patients Above 50 Years of Age With Minimum 2-Year Follow-up. Issue 5 (June 2018) - Hosogane, Naobumi; Ames, Christopher; Matsumoto, Morio; Yagi, Mitsuru; Matsuyama, Yukihiro; Taneichi, Hiroshi; Yamato, Yu; Takeuchi, Daisaku; Schwab, Frank; Shaffrey, Christopher; Smith, Justin S.; Bess, Shay; et al.
Abstract : Study Design: Retrospective review of North American and Japanese adult spinal deformity (ASD) database. Objective: To investigate the ethnical differences in radiographic parameters and Scoliosis Research Society (SRS)-22 between North American and Japanese ASD. Summary of Background Data: Previous comparison study between North American and Japanese ASD patients has revealed Japanese patients had marked pelvic tilt deformity and had lower Oswestry Disability Index scores corresponding to established thresholds of radiographic deformity. However, the subjects of the previous study included relatively younger ASD patients (above 18 y) of idiopathic origin. Materials and Methods: Total 282 ASD patients older than 50 years, 211 patients from North America (United States) and 71 patients from Japan (JP), with minimum 2-year follow-up postoperatively were included in the study. Radiologic parameters were compared at the baseline and at 2-year follow-up. SRS-22 score was used for the comparison of clinical outcome. Results: At baseline, Japan showed significantly worse sagittal alignment such as smaller lumbar lordosis (LL), larger pelvic incidence (PI), and larger sagittal vertical axis than United States. However, Japan had significantly fewer levels fused than United States (US, 12.66±4.6; JP, 8.49±2.7). At 2 years after the surgery, Japan still had significantly worse residual sagittal deformity. Comparison of SRS-22 scores revealed Japan had better pain but worse functional domain scores at baseline which improved to comparable levels to the United States at 2 years. Self-image and mental health scores in Japan were significantly worse both at baseline and at 2 years. Analysis of factors affecting SRS-22 satisfaction score at 2 years revealed that previous spinal fusion surgery in the United States and LL, PI-LL, and sagittal vertical axis at 2 years in Japan had significant correlation. Conclusions: These similarities and discrepancies may be influenced by the cultural or lifestyle differences between both nations and should be considered when interpreting the results of ASD studies among different ethnicities.